Influencing Curriculum Development and Knowledge of Climate Change Issues in Universities: The Case of University Of Nigeria Nsukka - N Ozor; M C Madukwe (Journal of Agricultural Extension, 2014)
The current institutional structures and academic programmes in most universities preclude effective education and capacity building on issues of climate change. Besides, the pedagogies and curricula are centrally defined by university governance structures which are very hierarchical and rigid, and in most cases, discourage the culture of shared thinking and collaboration required for addressing complex system-related challenges such as climate change. The study aimed at influencing curriculum development and knowledge of climate change issues at the University of Nigeria, Nsukka (UNN) and its environs. To realize this, a multi stakeholder dialogue was conducted to sensitize the stakeholders on the need to include issues of climate change in their respective Faculty curricula. Over 320 participants drawn from the academia, policymakers, private sectors and the civil society organizations participated in the process that culminated in a one-day workshop at UNN in 2009. An outcome mapping approach was used to identify the most important reasons for climate-proofing the courses in the relevant Faculties of the University through curriculum review. Results show that there is need to provide a clearer understanding of climate change issues; build capacity at individual and institutional levels for climate change adaptation; provide opportunity to attract donor funds for teaching, learning, research and community service; provide conducive environment for transdisciplinarity and shared thinking on climate change issues; and transform the future leaders of tomorrow (youths) by promoting the culture of innovation for climate change adaptation. Recommendations ranged from revising existing course contents to emphasize issues of climate change (short-term approach), introduction of entirely new course modules on climate change (medium-term approach) to introduction of new degree programmes (long term approach) in the relevant Faculties of the University. Finally, a communiqué calling for urgent inclusion of climate change issues in the curriculum of the UNN was adopted by the University Administration.